Highly ordered clustering of TNFα and BAFF ligand-receptor-intracellular adaptor complexes on a lipid membrane - Chan Seok Lim; Jisun Lee; Ji Won Kim; Jie-Oh Lee (Nature Communications)
Abstract The TNF family plays a critical role in immune regulation. Here, we present high-resolution structures of clusters formed by two TNF receptor family proteins, TNFR1 and BAFFR. Using a lipid monolayer method to mimic their membrane-bound state, we observe that the TNFα-TNFR1 complex forms highly ordered clusters of trimers on the lipid membrane. A non-competitive TNFR1 antagonist that inhibits receptor activation disrupted these clusters without blocking ligand binding or receptor trimerization. Furthermore, we find that the BAFF-BAFFR, BAFF-TACI, and BAFF-BCMA receptor-ligand complexes predominantly form pentagonal clusters of trimers on the lipid membrane. Notably, the binding of the intracellular adaptor TRAF3 to the BAFF-BAFFR complex induces a structural transition from a pentagonal to a flat hexagonal cluster. Mutations in BAFF that impair BAFFR activation prevented cluster formation. Our findings demonstrate that ligand binding induces the formation of highly ordered clusters of TNFR1 and BAFFR receptors on the lipid membrane, which is essential for their activation.